Disease characteristics, prognosis and miglustat treatment effects on disease progression in patients with Niemann-Pick disease Type C: an international, multicenter, retrospective chart review - Pineda, Mercedes; Juríčková, Katarína; Karimzadeh, Parvaneh; Kolnikova, Miriam; Malinova, Vera; Insua, Jose Luis; Velten, Christian; Kolb, Stefan A (Orphanet journal of rare diseases, 2019)
BACKGROUND: Niemann-Pick disease Type C (NP-C) is a lysosomal lipid storage disorder characterized by progressive neurodegenerative symptomatology. The signs and symptoms of NP-C vary with age at disease onset, and available therapies are directed at alleviating symptoms and stabilizing disease progression. We report the characteristics and factors related to disease progression, and analyze the effect of miglustat treatment on disease progression and patient survival using NP-C disability scales. METHODS: This retrospective, observational chart review included patients with NP-C from five expert NP-C centers. Patient disability scores were recorded using three published NP-C disability scales, and a unified disability scale was developed to allow comparison of data from each scale. Disease progression was represented by scores on the unified NP-C disability scale. Patients were stratified as infantile (< 4 years), juvenile (≥ 4 - < 16 years), and adult (≥ 16 years) based on age at diagnosis, and treated ≥1 year and non-treated/treated < 1 year based on the duration of miglustat treatment. RESULTS: The analysis included 63 patients; the majority (61.9%) were on miglustat therapy for ≥1 year. Ataxia and clumsiness/frequent fall were the most common neurologic symptoms across age groups, whereas, hypotonia and delayed developmental milestones were specific to infantile patients. In both infantile and juvenile patients, visceral signs preceded diagnosis and neurologic signs were noted at or shortly after diagnosis. Adult patients presented with a range of visceral, neurologic, and psychiatric signs in years preceding diagnosis. Patients on miglustat therapy for ≥1 year had a lower mean annual disease progression compared with those untreated/treated < 1 year (1.32 vs 3.54 points/year). A significant reduction in annual disease progression in infantile patients, and a trend towards reduced disease progression in juvenile patients after ≥1 year of miglustat treatment, translated into higher age at last contact or death in these groups. CONCLUSIONS: The type and onset of symptoms varied across age groups and were consistent with descriptions of NP-C within the literature. Miglustat treatment was associated with a reduced rate of disability score worsening in infantile and juvenile patients, both in agreement with increased age at last contact.
Keywords: Female; dítě; předškolní dítě; NP-C; Linear Models; ženské pohlaví; Niemann-Pick Disease, Type C; Adolescent; lidé; NP-C disability scales; Niemann-pick disease type C; 1-deoxynojirimycin; lineární modely; prognóza; retrospektivní studie; Male; Child, Preschool; Disease characteristics; Prognosis; Child; mužské pohlaví; Retrospective Studies; 1-Deoxynojirimycin; mladiství; Niemannova-Pickova nemoc typu C; Humans